KEEFEKTIFAN LAYANAN BIMBINGAN KELOMPOK UNTUK MENGANTISIPASI PRILAKU BULLYING PADA SISWA MTSM LAWANG TIGO BALAI - Rina Wati Putri; Syawaluddin; Susi Maria Sari (CV. ADIBA AISHA AMIRA, 2024)
Group tutoring is the provision of services in a group atmosphere by utilizing group dynamics. Group guidance is also a guidance activity given to a number of individuals carried out together, in order to help students in formulating and making the right decisions, group guidance is held to provide information of a professional, vocational and social nature. The aim of this research is to determine the effectiveness of group guidance services in anticipating bullying behavior among MTSM Lawang Tigo Balai students. Researchers used a quantitative research method approach with the type of pre-experiment, one group, pre-test, post-test. The subjects in the research were 10 children who volunteered to take part in group guidance. The data analysis technique uses the Wilcoxom rank test. The instrument used is a questionnaire. The Wilcoxom rank test analysis shows a value of 0.05, so it can be concluded that the implementation of group guidance services is effective in anticipating bullying behavior at MTSM Lawang Tigo Balai